An Analysis of Translational Shifts in the Original Soundtrack Translation of the Film ‘Rapunzel – Tangled (Lembaga Pengembangan Kinerja Dosen, 2026)
This study explores the translation shifts found in the soundtrack of the film Rapunzel – Tangled, specifically in the German-to-Indonesian translation. The objective is to identify the types of translation shifts and analyze their distribution and tendencies during the translation process. The research data were taken from three songs: